2015
DOI: 10.3329/bjsir.v50i3.25581
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on nutritional quality of commercial wheat flour in Bangladesh

Abstract: Cereal industry and its derived products have a large economic and social importance worldwide. Baking industries are extensively using wheat flour to produce various baked products. Therefore, in this investigation it is intended to study and determine proximate, physicochemical, functional properties of six brand of wheat flour in Bangladesh. The entire brand had moisture contents: 9.90-12.48%, protein: 8.67-12.47%, fat: 0.893-1.387% and ash content: 0.387-0.707%. The ACI brand had the highest amount of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 10 publications
(7 reference statements)
5
13
0
2
Order By: Relevance
“…The values were supported by the findings of Ahmad et al (2005). However, a wide variation was reported by Saeid et al (2015) for the CWF available in Bangladesh (8.67-12.47%), who suggested that this could be due to external factors associated with the crop, in addition to genetic makeup. Brown (1991) stated that soil nitrogen also can influence the protein level.…”
Section: Resultsmentioning
confidence: 99%
“…The values were supported by the findings of Ahmad et al (2005). However, a wide variation was reported by Saeid et al (2015) for the CWF available in Bangladesh (8.67-12.47%), who suggested that this could be due to external factors associated with the crop, in addition to genetic makeup. Brown (1991) stated that soil nitrogen also can influence the protein level.…”
Section: Resultsmentioning
confidence: 99%
“…Moisture content range between 9.0%-11.45% for different duration of treatment, among them moisture content of grain obtained from the plant from 6 min treated seed showed significant difference compare to others (Table 2). The moisture content of different wheat varieties is estimated to range from 9.90 to 12.48 percent 53 . Thus, plasma treatments slightly reduce moisture content; protect the grain from the microorganism.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows et al (2015). It was explained that higher fiber content and lower amount of starch might be related to higher WAI (Saeid et al, 2015). was significantly (p < .05) decreased with the addition of fig seed…”
Section: Physical Characteristics Of Gluten-free Cupcakes and Flour Propertiesmentioning
confidence: 99%